2005
DOI: 10.1152/japplphysiol.00284.2005
|View full text |Cite
|
Sign up to set email alerts
|

Spinal reflexes and coactivation of ankle muscles during a submaximal fatiguing contraction

Abstract: This study examined the involvement of spinal mechanisms in the control of coactivation during a sustained contraction of the ankle dorsiflexors at 50% of maximal voluntary contraction. Changes in the surface electromyogram (EMG) of the tibialis anterior and of two antagonist muscles, the soleus and lateral gastrocnemius, were investigated during and after the fatigue task. Concurrently, the compound action potential (M-wave) and the Hoffmann reflex of the soleus and lateral gastrocnemius were recorded. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
55
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 46 publications
7
55
0
3
Order By: Relevance
“…Previous researchers interpreted these phenomena to additional recruitment of motor units, an increased firing rate, and synchronization of motor units' recruitment [43]. Furthermore, Levenez et al [44] demonstrated that sustained dorsiflexion under 50% MVC induced decline of soleus H-reflex amplitude. Rossi et al [45] demonstrated that sustained MVC of abductor digiti minimi induced decline of the F-wave amplitude, although the F-wave persistence was unchanged.…”
Section: Discussionmentioning
confidence: 98%
“…Previous researchers interpreted these phenomena to additional recruitment of motor units, an increased firing rate, and synchronization of motor units' recruitment [43]. Furthermore, Levenez et al [44] demonstrated that sustained dorsiflexion under 50% MVC induced decline of soleus H-reflex amplitude. Rossi et al [45] demonstrated that sustained MVC of abductor digiti minimi induced decline of the F-wave amplitude, although the F-wave persistence was unchanged.…”
Section: Discussionmentioning
confidence: 98%
“…It is unlikely that this decrease in median frequency of the antagonist muscles was caused by increased extracellular metabolites because the cocontraction level was only about 10% of the agonist activity and peripheral fatigue was therefore not to be expected. Indeed, several studies have shown that the force generating capacity of the antagonist muscles remained equal after fatiguing contractions of the agonist muscles (e.g., Levenez et al 2005). Although the eVects on the EMG amplitude and median frequency of the antagonist muscle could, in principle, result from cross-talk, it is typically interpreted as an eVect of a common drive to the agonist-antagonist couple (Psek and Cafarelli 1993;Ebenbichler et al 1998;Mullany et al 2002;Levenez et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several studies have shown that the force generating capacity of the antagonist muscles remained equal after fatiguing contractions of the agonist muscles (e.g., Levenez et al 2005). Although the eVects on the EMG amplitude and median frequency of the antagonist muscle could, in principle, result from cross-talk, it is typically interpreted as an eVect of a common drive to the agonist-antagonist couple (Psek and Cafarelli 1993;Ebenbichler et al 1998;Mullany et al 2002;Levenez et al 2005). In support of this interpretation, an increase in amplitude and a decrease in median frequency have been found in the contralateral homologous muscle after unilateral muscle fatigue (Morrison et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This intensity was then increased by 10% and kept constant throughout the experiment. Such supramaximal stimulation intensity, as used in previous studies (46,53,56), limits the discomfort associated with the stimulation compared with higher supramaximal levels. Pulse width was set at 0.1 ms for the upper limbs (68) and at 1 ms for the lower limbs (53,57).…”
Section: Data Collectionmentioning
confidence: 99%